2018
DOI: 10.12693/aphyspola.133.336
|View full text |Cite
|
Sign up to set email alerts
|

Particle-Hole Symmetry of Charge Excitation Spectra in the Paramagnetic Phase of the Hubbard Model

Abstract: The Kotliar and Ruckenstein slave-boson representation of the Hubbard model allows to obtain an approximation of the charge dynamical response function resulting from the Gaussian fluctuations around the paramagnetic saddle-point in analytical form. Numerical evaluation in the thermodynamical limit yields charge excitation spectra consisting of a continuum, a gapless collective mode with anisotropic zero-sound velocity, and a correlation induced high-frequency mode at ω U . In this work we show that this analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…These two fields are at the first place associated with charge fluctuations, and one might wonder whether the charge fluctuation spectrum depends on this asymmetry, but it could be shown that this is not the case, at least when it is computed to one-loop order around the paramagnetic saddle-point. [67,87] In this context this one-loop calculation was believed to coincide with the time-dependent Gutzwiller approximation until discrepancies between the two were put forward. [67] This motivated an extension of it to achieve agreement with the slave boson one-loop calculation.…”
Section: Introductionmentioning
confidence: 99%
“…These two fields are at the first place associated with charge fluctuations, and one might wonder whether the charge fluctuation spectrum depends on this asymmetry, but it could be shown that this is not the case, at least when it is computed to one-loop order around the paramagnetic saddle-point. [67,87] In this context this one-loop calculation was believed to coincide with the time-dependent Gutzwiller approximation until discrepancies between the two were put forward. [67] This motivated an extension of it to achieve agreement with the slave boson one-loop calculation.…”
Section: Introductionmentioning
confidence: 99%
“…These fields are primarily associated with charge fluctuations, and one might wonder about the consequences of this asymmetry on the charge fluctuation spectrum. It turns out that the latter is independent of the choice, at least when computed to one-loop order around the paramagnetic saddle-point [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…It may be chosen to be the d field, which accounts for doubly occupied sites, or the e field, which accounts for empty sites. These two fields are at the first place associated with charge fluctuations, and one might wonder whether the charge fluctuation spectrum depends on this asymmetry, but it could be shown that this is not the case, at least when it is computed to one-loop order around the paramagnetic saddle-point [67,87]. In this context this one-loop calculation was believed to coincide with the time-dependent Gutzwiller approximation (TDGA) until discrepancies between the two were put forward [67].…”
Section: Introductionmentioning
confidence: 99%